Effects of irrigation and nitrogen topdressing on water and nitrogen use efficiency for winter wheat with micro-sprinkling hose irrigation in North China - Xiaojun Shen; Junming Liu; Ling Liu; Ketema Zeleke; Ruochen Yi; Xiaopei Zhang; Yang Gao; Yueping Liang (Agricultural Water Management, 2024)
In order to explore the efficient use of water and nitrogen for winter wheat under irrigation with micro-sprinkling hose, two-season field experiments were conducted to evaluate the effects of irrigation levels and nitrogen application rate on yield, water productivity (WP) and nitrogen partial factor productivity (NPFP). Three irrigation levels were 60 %, 65 %, and 70 % field capacity (FC) during the reviving to jointing stage, 65 %, 70 %, and 75 % FC after the jointing stage, referred to as W1, W2 and W3, respectively. The irrigating water quota is 30 mm. The five N topdressing period treatments were reviving period + booting stage (N1), jointing + booting stage (N2), reviving period (N3), jointing stage (N4), and booting stage (N5). The results showed that the water consumption, leaf area index, plant height, biomass, grain yield, and NPFP increased with an increase in irrigation amount, and the WP decreased with an increase in irrigation amount. Nitrogen applied during the reviving period was beneficial for increasing grain yield, WP, and NPFP under the irrigation level W1; nitrogen applied during the jointing period was beneficial for increasing grain yield, WP, and NPFP for winter wheat under the W2 and W3 irrigation levels. The W3N2 treatment resulted in the highest grain yield (8.98 t·ha−1), but it was not significant difference from W2N2 (average of 8.92 t·ha−1). After a comprehensive evaluation based on grain yield, WP and NPFP, the appropriate modes of irrigation and nitrogen is the treatment of W2N2 (65 % and 70 % FC irrigation treatments during the reviving to jointing stage and the stages after jointing stage, respectively; the nitrogen topdressing during jointing + booting stage) for winter wheat using micro-sprinkling hose irrigation in North China.